Dampak Psikologis Jangka Panjang Kekerasan Seksual Anak (Komparasi Faktor: Pelaku, Tipe, Cara, Keterbukaan Dan Dukungan Sosial) - Rini Rini (Universitas Persada Indonesia YAI, 2020)
The significant increase in the number of child sexual abuse in Indonesia from 2016 to 2019requires serious attention and handling. The most common negative effect felt by victims ofsexual abuse is psychological damage. This damage can have both short and long term negativeimpacts. Several factors that can strengthen the long-term effects of sexual abuse are the factorsof the perpetrator of sexual abuse, the type of sexual abuse experienced, how sexual abuse iscarried out, the openness of the victim after sexual abuse, and the social support the victimreceives. Respondents of this study were 300 adults who had experienced sexual abuse duringchildhood, using accidental sampling technique. Data collection uses google form which isdistributed via WhatsApp, Telegram, Facebook, and email. Data analysis used are IndependentSample T-Test and Oneway Anova. The results of the analysis show that there are significantdifferences in the long-term psychological impact of victims of child sexual abuse in terms of thefactors of the perpetrator of the abuse, the type of abuse, the way the abuse was carried out, theopenness of the victim and the social support received by the victim.